Analysis of Factors Influencing the Decision to Visit Mandalika for Domestic Tourists - Sipahutar, Dayan Hakim Natigor; Yusron, Ulin Niam; Sipahutar, Putri Sion H (Dinasti Publisher, 2025)
The factors that influence tourists' decisions to visit the Mandalika area are crucial for tourism stakeholders in developing tourism marketing strategies in Mandalika. If tourism stakeholders can identify these factors, it will be easier to focus marketing strategy planning on consumer needs, thus increasing the likelihood of Mandalika being chosen by domestic tourists. This study aims to determine the factors influencing domestic tourists' decisions to visit the Mandalika area and to identify the most important or dominant factors influencing their decision to visit the Mandalika area. The primary objective of this research is to provide stakeholders with a foundation for developing tourism marketing strategies that align with the most important needs and desires of domestic tourists in Indonesia. This study began by listing the 24 factors most frequently considered by domestic tourists when selecting a tourist destination. Then, using the Cochran Q Test iteration method, 15 factors were identified as the most important, with Personal Motivation ranking number one among the most important factors to consider when choosing a tourist destination.